Participatory reading in late-medieval England - Blatt, Heather (Manchester Medieval Literature and Culture, 2017)
This book explores how modern media practices can illuminate participatory reading in England from the late-fourteenth to the early-sixteenth centuries. Nonlinear apprehension, immersion and embodiment are practices intimately familiar to readers of Wikipedia, players of video games and users of multi-touch mobile devices. But far from being unique to digital media, they have clear analogues in the pre-modern era. Participatory reading in late-medieval England traces how the affinities between old and new media can reveal fresh insights not only about the digital, but also about the long history of media forms and practices. It thus casts new light on the literary practices of a period pre- and post-print to demonstrate how participatory reading vitally contributed to and shaped these negotiations of fragile authority.